Analisis Efektivitas Aplikasi Cek DJP Online Pajak dan Laporan SPT Tahunan E-filling Menggunakan Framework COBIT 5 Domain EDM (Evaluate, Direct, and Monitor) pada KPP Pratama Tanjungpinang - Liza Safitri; Arpelasari (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
Kantor Pelayanan Pajak Pratama Tanjungpinang use e-filling application in the tax payment process and make it easy to service tax payers. To know how far of information technology on going, so we take measurement of capability and rating scale of information technology who’s being applied. The purpose of this measurement is to know how far of information technology who’s being applied so we can recommend to improve performed of company. This research method is data analysis quantitative and validity test. In collection of data used with literature review and field studies (interview, observation, questionnaire). The results of data collection based on framework COBIT 5 we got optimization of TI on going (EDM01) capability level got the value 5.00 and the rating scale value of five’s level (optimizing process) has a status fully achieved of 90.2%. For the managerial service optimization process (EDM02) the capability level got the value 5.00, and the rating scale value of five’s level (optimizing process) has a status fully achieved of 91.4%. The risk management process (EDM03) capability level got the value of 5.00, and the rating scale value of five’s level (optimizing process) has a status fully achieved of 92.4%. The resource optimization process (EDM04) capability level got the value 5.00, and the rating scale value of five’s level (optimizing process) has a status fully achieved of 90.6%. For the performance optimization process (EDM05) the capability level got the value 5.00, and the rating scale value of five’s level (optimizing process) has a status fully achieved of 90.4%.